Identification and characterization of Fusarium spp. causing slow decline disease of black pepper (piper nigrum) in Belaga and Betong districts, Sarawak - Shahidan, Shahidan F.N.; Kwan, Y.M. (Malaysian Society of Plant Physiology (MSPP), 2021)
Black pepper (Piper nigrum L.) is an ancient spice and medicinal plant native to the Western Ghats of Kerala, India. It is one of the most heavily consumed spices in the present day, accounting for almost one third of the global spice market. Black pepper is extensively used in food and beverage and is often considered as a functional food owing to its potential health benefits and therapeutic potential against diseases. In addition to its fundamental nutrition value, piperine (the bioactive compound of black pepper) is used widely in various insecticides, cosmetic, and pharmaceutical products due to its strong pungent aroma, antioxidant, and antimicrobial properties (Abdulazeez et al., 2016). More recently, black pepper essential oil has been developed as a natural food preservative in food packaging because of its antimicrobial properties (Myszka et al., 2017). Black pepper is mainly exported in black and white peppercorns (95%), with the remaining 5% in the form of powder, oil, and oleoresin. Black pepper global market valued at USD3.7 billion in 2017 and is estimated to reach USD5.7 billion by 2024 (Persistence Market Research, 2017). Thus, it is known as the ‘King of Spices’ due to its high economic value. Malaysia is currently the eighth largest world black pepper producer, with an export volume that amounted to 19,200 tonnes, equal to RM145.6 million export revenue in 2019 (DOA, 2020). Sarawak remains the largest black pepper producer in Malaysia contribute to nearly 98% of its production. Besides, black pepper is an important cash crop contributes to the income and livelihood of approximately 67,000 farmers in rural areas of Sarawak (DOA, 2020). Fungal diseases are important factors that affect black pepper production under the warm and humid climate in Sarawak. It has become one of the major constraints and resulted in the reduction of black pepper yield. Slow decline or yellowing disease caused by the combined infestation by nematode (Radopholus spp. and Meloidogyne spp.) and Fusarium spp. has resulted in an annual reduction in black pepper production as high as 30% (Ramana and Eapen, 2000). In this disease complex, the nematodes enter the plant roots as larvae and provide ingress for fungal infection. The infected plants are usually stunted, it starts with leaf yellowing, wilt and drops off progressively upward from older leaves to young leaves, leaving only the bare stem. Brownish-black lesions appear on the shoots, vascular bundle, and infected plants (Wong, 2010). Infected plants will reduce in productivity and, consequently, death within one to a few years. Several Fusarium species were reported to cause slow decline disease in black pepper. There is the necessity to study the identity of the causal fungus of slow decline disease in Sarawak. Accurate identification of the fungal species would enable the employment of effective disease control and prevention strategies. Morphological characterization based on colony appearance, pigmentation, shape, and size of macro- and microconidia, and chlamydospore presence are among the most common methods to identify Fusarium species. Nevertheless, the differentiation of Fusarium species based on morphological characteristics is imprecise due to the close similarity between species. The polymerase chain reaction (PCR) technique remains the most accurate tool for discriminating fungal species and intraspecific differentiation among the isolated species. This study aims to i) isolate Fusarium spp. from symptomatic black pepper plants and ii) characterize Fusarium isolates using morphological characteristics and phylogenetic analysis through the sequence analysis of the translation elongation factor 1-alpha (TEF-1α) gene.